Role of Government Sponsored Health Insurance Schemes in Public Health Management in Tamil Nadu - Pugazhenthi, V.; Sunitha, C. (Prabandhan: Indian Journal of Management, 2015)
Providing adequate health cover to the citizens becomes an inevitable identity of a welfare state because of which countries all over the world, developed or developing, are eyeing universal health coverage either by providing government sponsored treatments or by government sponsored health insurance schemes or both. In this context, the Government of Tamil Nadu is considered as one of the best performing welfare states in India. In addition to the wide public health delivery system, the Government of Tamil Nadu presently sponsors two insurance schemes namely, Chief Minister's Comprehensive Health Insurance Scheme and New Health Insurance Scheme, 2012 to avail the services of the private sector as well. These two schemes were evolved from three other schemes. The features and performances of these five schemes are described in the present research paper in detail. The paper also provides a host of recommendations and policy measures.